DOI: 10.29007/1shp
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Automation and Robotics in Construction

Abstract: Automation and robotics have been widely adopted across many industries, but the construction industry has not achieved the same level of diffusion. Construction is a critical global industry that is challenged to address issues of productivity, safety, quality, and profitability. Automation and robotics have a tremendous potential impact on all these fronts. The objective of this study is to identify barriers to the adoption of automation and robotics in the construction industry as perceived by industry expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The findings revealed that deployment of R&A for safer construction worksites in South Africa is impeded by four major groups of industry, technology, human and costrelated factors. These grouped factors are consistent with existing literature that have grouped the barriers to the use of R&A and related technologies in both developed and developing countries worldwide (Delgado et al, 2019;Huang et al, 2021;Oke et al, 2021;Trujillo and Holt, 2020). However, while Oke et al (2021) submitted that cost and technologyrelated issues are the major barriers to the use of robotics in the construction industry in Nigeria, this current study found that the barriers exceed these two groups to include industry and human-related factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings revealed that deployment of R&A for safer construction worksites in South Africa is impeded by four major groups of industry, technology, human and costrelated factors. These grouped factors are consistent with existing literature that have grouped the barriers to the use of R&A and related technologies in both developed and developing countries worldwide (Delgado et al, 2019;Huang et al, 2021;Oke et al, 2021;Trujillo and Holt, 2020). However, while Oke et al (2021) submitted that cost and technologyrelated issues are the major barriers to the use of robotics in the construction industry in Nigeria, this current study found that the barriers exceed these two groups to include industry and human-related factors.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have attempted to unearth these factors and categorise them based on their severity for clarity. For instance, in the USA, Trujillo and Holt (2020) categorised the barriers to using robotics into three main groups, namely, cultural, technical and teams' issues. It was noted that while literature has placed focus on the technical aspect of this technology as key deterrents to its usage, the culture at the organisational level and the team needed to handle this technology are key factors to consider.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the presence of these aforementioned studies on the knowledge of robotics and automation systems in the construction industry, very few have sought to identify and evaluate the barriers hindering the adoption of robotics and automation systems in the construction industry. Existing studies have been conducted in European countries (Delgado et al, 2019), United States of America (RECM et al, 2020;Pradhananga et al, 2021), Switzerland (Chen et al, 2018), Malaysia (Kamaruddin et al, 2016;Yahya et al, 2019), Pakistan (Imtiaz et al, 2021), India (Mistri and Rathod, 2015) and South Africa (Aghimien et al, 2022). Despite the presence of these studies, very few have been conducted in the Nigerian construction industry, a gap that this study seeks to fill.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies expect a significant increase in the use of robots in construction projects in the next few years (Liang et al 2020 ), and despite the presence of some cases where robots have been used in construction sites since the 1980s (Forcael et al 2020 ), robotics face several barriers to be normalized in the construction industry. In addition to the impact of the cost and time-related barriers, the lack of sufficient knowledge about new managerial principles and technological advances, lack of skilled team, resistance to change and to adopt new practices and technologies by managers and employees, and poor leadership are among the most affecting factors to adopt construction 4.0 and robotics in the construction industry (Al balkhy et al 2021 ; Albalkhy and Sweis 2020 ; Trujillo and Holt 2020 ; Mahbub 2015 ; Davila Delgado et al 2019 ; Buchli et al 2018 ; Carra et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%